1997
DOI: 10.1007/s11746-997-0156-3
|View full text |Cite
|
Sign up to set email alerts
|

Spectral confirmation of trans monounsaturated C18 fatty acid positional isomers

Abstract: The trans octadecenoic acid methyl ester isomers were obtained from a partially hydrogenated soybean oil sample and isolated by silver-ion high-performance liquid chromatography. The double bond configuration was confirmed to be trans by using gas chromatography-direct deposition-Fourier transform infrared spectroscopy. The double bond positions for nine individual trans octadecenoic acid positional isomers were confirmed by gas chromatography-electron ionization mass spectrometry after derivatization to 2-alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 13 publications
1
32
0
Order By: Relevance
“…This spectrum forms the pattern predicted from the work of Zhang et al [31] for trans-8 C18:1 and is nearly identical to that reported for this isomer by Mossoba et al [14], with two prominent ions (m/z 168 and 222) and a gap of 12 atomic mass units between m/z =182-194 to locate the double bond. Spectra from trans-6 and trans-7 C18:1 DMOX exhibit different ion profiles [3,14]. The pattern observed in Figure 1 was similar for the same peak in the five ovine herds studied.…”
Section: Mutfa Content and Profilesupporting
confidence: 88%
“…This spectrum forms the pattern predicted from the work of Zhang et al [31] for trans-8 C18:1 and is nearly identical to that reported for this isomer by Mossoba et al [14], with two prominent ions (m/z 168 and 222) and a gap of 12 atomic mass units between m/z =182-194 to locate the double bond. Spectra from trans-6 and trans-7 C18:1 DMOX exhibit different ion profiles [3,14]. The pattern observed in Figure 1 was similar for the same peak in the five ovine herds studied.…”
Section: Mutfa Content and Profilesupporting
confidence: 88%
“…The ∆13t/∆14t pair was finally resolved in 1997 independently by two groups [9,37] by lowering the isothermal temperature to 140°C for the higher molecular dimethyloxazolidine (DMOX) derivatives [37], and to 125°C for the FAME derivatives [9]. Naturally these conditions greatly increased the analysis times to nearly 3 h for the separation for the C18:1 [7,9,37] and 6 h for the C20:1 isomers [7]. Fig.…”
Section: Separation Of T-c18:1 Isomersmentioning
confidence: 99%
“…Using the normal high temperature method for forming DMOX derivatives, the C-2 isomer can isomerize to the C-3 isomer and vice versa, but a relatively mild method minimizes isomerizaton [12]. GC-MS of DMOX derivatives was used to characterize the trans monoenoic positional isomers in partially hydrogenated soybean oil [13] and, in combination with GC of methyl esters, the trans and cis monoenes in foods that contained hydrogenated oils and ruminant fats [14].…”
Section: Picolinyl Ester Versus 44-dimethyloxazoline Derivativesmentioning
confidence: 99%